Electrodeposition of PbTe thin films: electrochemical behavior and effect of reverse pulse potential. (10th August 2015) - Frantz, Cédric; Vichery, Charlotte; Michler, Johann; Philippe, Laetitia
Highlights: The electrochemical behavior of Pb 2+, Te IV /PbTe is described in details. Current transient curves are analyzed for different applied potentials. The dependence of the film characteristics on the applied potential is presented. Near-stoichiometric deposits are usually dendritic. The effect of reverse pulse potential is displayed. Abstract: This paper reports on the voltammetric behavior of gold substrates in acidic nitrate electrolytes containing HTeO2 + and Pb 2+ . Particular anodic behavior is highlighted and studied by anodic stripping experiments, demonstrating that the presence of PbTe dendrites induces an additional anodic peak prior to the dissolution of bulk PbTe. The diffusion coefficients of Pb 2+ and HTeO2 + were measured in order to adjust their respective concentration in the electrolyte. Diffusion of Pb 2+ being slightly faster than HTeO2 +, optimal concentrations were calculated to be 4.1 mM Pb 2+ for 5 mM HTeO2 + . For steady state potentiostatic deposition, Pb is underpotentially deposited onto overpotentially deposited Te 0 from -175 mV and its content in the deposit slightly increases with the applied overpotential. However, increasing the overpotential also induces dendritic morphologies. In contrast, reverse pulse deposition can lead to the formation of spherical assemblies of hollow trigonal nanorods with high specific area. However, it strongly decreases the Pb content in the film.